Antigen-Specific Cellular and Humoral Responses Are Induced by Intradermal Mycobacterium leprae Infection of the Mouse Ear - Duthie, Malcolm S. (American Society for Microbiology (ASM), 2007)
Leprosy is caused by infection with Mycobacterium leprae. The immune response of leprosy patients can be highly diverse, ranging from strong cellular responses accompanied by an apparent deficit of M. leprae-specific antibodies to strong humoral responses with a deficit of cell-mediated responses. Leprosy takes many years to manifest, and this has precluded analyses of disease and immune response development in infected humans. In an attempt to better define development of the immune response during leprosy we have developed an M. leprae ear infection model. Intradermal inoculation of M. leprae into the ear supported not only infection but also the development of a chronic inflammatory response. The inflammatory response was localized, comprising a T-cell infiltration into the ear and congestion of cells in the draining lymph nodes. The development of local chronic inflammation was prevented by rifampin treatment. Importantly, and in contrast to subcutaneous M. leprae footpad infection, systemic M. leprae-specific gamma interferon and antibody responses were detected following intradermal ear infection. These results indicate the utility of intradermal ear infection for both induction and understanding of the immune response during M. leprae infection and the identification or testing of new leprosy treatments.